2016
DOI: 10.5539/elt.v9n10p133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alignment on Text Cohesion in the Continuation Task

Abstract: A continuation task provides learners with a text with its ending removed and requires them to complete it through writing in a most coherent and logical way. The current study investigated (a) whether the continuation task had a positive effect on text cohesion and (b) whether texts produced by pairs exhibited higher cohesion than those produced by individual learners. A total of 80 college students were randomly assigned to one of three task conditions: 1) 40 students working in pairs in a continuation task;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Study suggested that learners continuing the English-version story made significantly fewer errors than those did the Chinese-version task, which verified the entailment of alignment in the continuation task. Besides, a good number studies have investigated how the alignment in the continuation task manipulates, such as alignment effects in the translation continuation task (Xu, 2016), effect of alignment on text cohesion (Jiang, 2016), and effects of alignment in the continuation task on L2 Chinese writing (Wang, 2016).…”
Section: Studies On the Continuation Taskmentioning
confidence: 99%
“…Study suggested that learners continuing the English-version story made significantly fewer errors than those did the Chinese-version task, which verified the entailment of alignment in the continuation task. Besides, a good number studies have investigated how the alignment in the continuation task manipulates, such as alignment effects in the translation continuation task (Xu, 2016), effect of alignment on text cohesion (Jiang, 2016), and effects of alignment in the continuation task on L2 Chinese writing (Wang, 2016).…”
Section: Studies On the Continuation Taskmentioning
confidence: 99%